Comparative efficacy and safety of mycophenolate mofetil and azathioprine in combination with corticosteroids in the treatment of lymphocytic myocarditis. (14th October 2021) - Blagova, O; Rud', R S; Novosadov, V M; Zaitsev, A Y U; Kogan, E A
Abstract: Purpose: To compare of the efficacy and safety of mycophenolate mofetil (MM) and azathioprine in combination with corticosteroids in the treatment of lymphocytic myocarditis. Methods: The study included 45 patients with lymphocytic myocarditis, 34 male, the average age 48.1±11.2 years. The diagnosis of myocarditis is verified by endomyocardial biopsy. In ten patients of both groups, the parvovirus B19 DNA was detected in the myocardium. All patients had heart failure 3 [3; 3] NYHA class. High immune activity was indicated by the presence of anti-heart antibodies in all patients. Group 1 included twenty-six patients who received MM 2 g per day. Twenty of them were naive; six patients received MM instead of azathioprine, which was canceled due to cytopenia and/or insufficient effect. Group 2 included nineteen patients who received azathioprine at an average dose of 100 [75; 150] mg per day. Patients of both groups also received methylprednisolone in an average starting dose 24 [24; 32] mg per day and standard therapy for heart failure. Initial group distribution was random. Patients in both groups did not differ significantly in baseline parameters. The mean follow-up period was 23 [8; 57] months (12 and 34 months in the groups). The study is approved by the university ethics committee. Results: The level of anti-heart antibodies significantly decreased in both groups. In both groups there was a significant improvement in the structural and functional parameters of the heart: NYHA class decreased from 3 [2.75; 3] to 2 [1; 2] (group 1, p<0.001) and from 3 [3; 3] to 2 [1; 2] (group 2, p<0.001), LV EF increased initially from 30.6±7.8 to 40.1±7.5% (group 1, p<0.001) and from 27.9±8.1 to 37.1±7.6% (group 2, p<0.01), by the end of follow-up to 45.9±9.0% (group 1, p<0.001) and to 42.4±13.7% (group 2, p<0.01). LV EDD significantly decreased from 6.4±0.6 to 6.1±0.8 cm (p<0.01), left atria size from 4.9±0.7 to 4.3±0.6 cm (p<0.05) and pulmonary arteria systolic pressure from 37.8±12.3 to 29.3±7.6 (p<0.05) only in the group 1. No direct side effects of MM were noted. Cytopenia due to treatment of azathioprine developed in 3 patients and required its replacement. There were no significant differences between groups 1 and 2 in overall mortality (7.7 vs 15.8%) and the transplant + death rate (7.7 vs 21.1%). The better survival in the MM group may be due to a shorter follow-up period. Conclusion: In patients with lymphocytic myocarditis, a combination of moderate doses of corticosteroids with MM is at least no less effective and safe than steroids with azathioprine. With a shorter follow-up period, the tendency to lower mortality and a more pronounced improvement in structural parameters with better tolerance was noted in the MM group. MM should be considered as an alternative option in the treatment of isolated lymphocytic myocarditis. Funding Acknowledgement: Type of funding sources: None.